Faba bean (Vicia faba L.) in natura mycorrhizal status evaluation and broad bean cropland soil biological fertility - Abdedjelil, Anissa Chahrazed; Kadiri, Amina; Ighilhariz, Zohra (Journal of Agriculture and Applied Biology, 2025)
The Broad bean (Vicia faba L.) is a legume with many virtues, commonly cultivated in the Mediterranean region, especially in Algeria, valued for its high nutritional properties and role in crop rotation systems. Moreover, as a natural green fertilizer, estab-lishing symbiotic relationship with arbuscular mycorrhizal fungi found in the soil, faba bean brings significant agronomic benefits, promotes biodiversity and contributes to soil preservation by limiting erosion. This study was conducted in a faba bean cropland site in the northwestern region of Algeria (Sebkha-Wilaya of Oran) in 2022 to assess in natura plant roots mycorrhi-zal colonization, soil characteristics and its biological fertility through mycorrhizal soil infectivity (MSI) and the spore’s abun-dance estimation. Physical and chemical properties analysis showed that the soil had a fine loamy-clay texture, with an alka-line pH, and low phosphorus content. It was moderately poor in organic matter and total nitrogen with less than 12 C/N ratio. In natura Vicia faba L. root fragments mycorrhizal colonization rate was very high (100%) with a highly mycorrhizal intensity (80.45%) and an arbuscular structures abundance (99.28%). Spores extracted from rhizosphere soil sample density were 1657±15.09 spores/100 g. Furthermore, results showed that Vi-cia faba rhizosphere cropland soil was high mycorrhizal infectiv-ity was high with 2.36±1.02g MSI Units/100 g. All results strong-ly suggested that Sebkha Vicia faba cropland soil has a good bio-logical fertility with a significant spore density. These results support the characterization of the soil as a potential biofertiliz-er.